Scales and instruments for measuring self-esteem in adolescents and young adults - Ochoa-Corral, Dulce M.; Campos-Valdez , Guadalupe; Gómez-Zarco , Alberto; Lima-Quezada, Alejandra (Journal of Basic and Applied Psychology Research, 2021)
Self-esteem is an evaluation the individual makes about themself, being classified as positive or negative. To accomplish this, psychology has proposed, use valid and reliable measuring instruments in the Mexican population, since there is a primary need to understand the different levels of self-esteem in individuals. The objective of the study was composing a review of validated scales and psychological instruments in the Mexican population on Self-esteem in adolescents and young adults from 15 to 25 years old. To the Method, the collection of information was made through databases such as PUBMED, Redalyc, Google Academic, Scielo and Dialnet. The descriptors were Self-esteem, adolescence, youth, and instruments of psychological evaluation. 96 articles were found, which only 5 of them fulfill the criteria. The results reflect 5 scales and instruments that measure self-esteem in Mexican adolescents and young adults, the application of these instruments fluctuates from 14 to 51 years and presents a reliability >0.70. It is concluded that in Social Sciences and Psychology, the application of instruments provides objective measures for a variety of problems to deal with. For this reason, valid and reliable self-esteem scales in the Mexican population may smooth the progress of the selection depending on subscales or factors that the psychologist or researcher wants to address individually or in a group.